Long-Term Survival Outcomes and Comparison of Different Treatment Modalities for Stage I-III Cervical Esophageal Carcinoma - Lu, Yanwei; Xu, Chenwang; Wang, Haitao; Song, Tao; Wu, Shixiu; Liang, Xiaodong; Xu, Hong'en (Frontiers in Medicine, 2021)
Purpose: To investigate the survival outcomes, prognostic factors and treatment modalities of stage I-III cervical esophageal carcinoma (CEC) patients using data from the Surveillance, Epidemiology, and End Results (SEER) database from the period 2004-2016. Methods: Patients with a histopathologic diagnosis of CEC were included. The primary endpoint was overall survival (OS). Univariate and multivariate analyses of OS were performed using Cox proportional hazards models, and OS was compared using the Kaplan-Meier method and log-rank test. Results: A total of 347 patients in the SEER database were enrolled. The median OS was 14.0 months, with a 5-year OS rate of 20.9%. The parameters that were found to significantly correlate with OS in the multivariate analysis were age at diagnosis (P< 0.001, hazard ratio (HR)= 1.832), sex (P< 0.001, HR= 1.867), histology (P= 0.001, HR= 0.366), surgery at the primary site (P= 0.021, HR= 0.553), radiotherapy (RT, P= 0.017, HR= 0.637) and chemotherapy (CT, P< 0.001, HR= 0.444). Comparison among the three treatment modalities demonstrated that a triple therapy regimen consisting of surgery, RT and CT was associated with a longer survival time than the other two treatment modalities before and after propensity score matching (PSM). However, triple therapy showed no significant survival benefit over double therapy (P= 0.496 before PSM and P= 0.184 after PSM). Conclusions: The survival of patients with CEC remains poor. Surgery, RT and CT were all strongly correlated with OS. We recommend a triple therapy regimen for select CEC patients based on the findings of the current study, although this recommendation should be further confirmed by prospective studies with large sample sizes.